2022
DOI: 10.4037/ajcc2022312
|View full text |Cite
|
Sign up to set email alerts
|

Critical Care Nurses’ Experiences During the COVID-19 Pandemic: A US National Survey

Abstract: Background Given critical care nurses’ high prepandemic levels of moral distress and burnout, the COVID-19 pandemic will most likely have a tremendous influence on intensive care unit (ICU) nurses’ mental health and continuation in the ICU workforce. Objective To describe the experiences of ICU nurses during the COVID-19 pandemic in the United States. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
109
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(124 citation statements)
references
References 18 publications
13
109
2
Order By: Relevance
“…26 A study in the US found that nurses perceived inadequate leadership support and inequity within the healthcare team. 3 Theme two: Balance of meeting patient and nurse needs and managing exhaustion. The agency described in this article used numerous support strategies including employee assistance for childcare and stress reduction programs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…26 A study in the US found that nurses perceived inadequate leadership support and inequity within the healthcare team. 3 Theme two: Balance of meeting patient and nurse needs and managing exhaustion. The agency described in this article used numerous support strategies including employee assistance for childcare and stress reduction programs.…”
Section: Discussionmentioning
confidence: 99%
“…1 Nurses have experienced practice changes, fear for themselves and their families, and moral distress from the inability to provide optimal care. [2][3][4] Throughout this time, it has been important for nurse leaders to provide the needed support to nurses.…”
Section: Nurse Experience During the Covid-19 Pandemicmentioning
confidence: 99%
See 1 more Smart Citation
“…The sheer numbers of patients, as well as the time needed to put on and remove personal protective equipment, meant that the time available for each patient was inevitably less than normal, and many staff members felt they were unable to provide the quality of care that they would under non-pandemic conditions. Lack of effective treatments, difficulties communicating with patients and their relatives, the need to make rapid, complex ethical decisions regarding which patients to admit or when to withhold or withdraw treatment, responsibility for new, non-ICU-trained members of the team transferred from other units, and fears about catching the virus and passing it on to their own family members, all added to the psychological burden on ICU teams with high rates of insomnia, depression, anxiety, post-traumatic stress disorder, and burnout [ 38 , 39 , 40 , 41 , 42 , 43 ]. Various strategies have been proposed to try and limit some of the psychological impact, including adequate training and senior support for new or re-allocated staff, availability of clinical psychologists for individual assessments and consultation, and regular team debriefing and support sessions [ 44 , 45 ].…”
Section: Psychological Impact On Healthcare Workersmentioning
confidence: 99%
“…A national US survey of critical care nurses reported physical and emotional symptoms of exhaustion, anxiety, sleeplessness, and moral distress. 1 Working conditions have become increasingly demanding during the pandemic, patient acuity is high, the nursing shortage continues, nurse-to-patient ratios regularly exceed recognized standards, nurses are working extreme amounts of overtime, and many nurses have seen too much death, feel disrespected and undervalued, and are frustrated that they cannot provide the level of excellent care required for positive patient outcomes. In other words, many of you are working in unhealthy and unsafe work environments.…”
mentioning
confidence: 99%